Gender Equality in Media Television (Semiotics Analysis of Fair and Lovely Advertisement Issue of Marriage or Master Degree) - Dwita, Desliana (Universitas Muhammadiyah Surakarta, 2018)
In many developing countries, most of television advertisements portray a general perception of patriarchy where men take decision for women and no place for gender equality. This work describes an analysis on a courageous ?Fair and Lovely? advertisement in Indonesia that conveys the message of gender equality. A semiotics analysis, qualitative?interpretative method, was used to analysis the signs related to gender equality messages in the episode about choosing between marriage and master degree. It is found that a women was pictured as someone who is confident, expressed bold opinions, like to discuss and exchange ideas, firm and straight forward in speaking, and wise in making a decision. In general, the visual signs used in the ?Fair and Lovely? advertisement convey a message that women should be equal with men especially in education and careers.??????????? Keywords :Advertisement, Gender Equality, Semiotic Analysis Roland Barthes.